A reading and description of the manuscript: “Al-Marsa’ Fi Differfteen Madhabs” Written by: Ahmed bin Ahmed bin Salama Shihab Al-Din Al-Qalyubi Al-Masry. 1069 AH. - Mohamed Ben Hadj Djelloul; Boufateh Tayeb (Journal of Science and Knowledge Horizons, 2022)
Knowing the art of disputes is of great importance, and of great benefit; By it the minds of stallions and spectators were liberated from the impurities of imitation, their minds excelled in theorizing and repetition, and their enthusiasm has excelled in rooting and innovation, and by which he distinguishes between the scholar and the ignorant, and between the initiator and the finished, until he was made the test of knowledge and its standard in knowing the differences and the forms of agreement, which is what it attests to. Al-Tabe’i Qatada said: “He who does not know the difference does not smell his nose in jurisprudence. "" ( )For this motive prompted the early and later to take care of this type of forensic science, learning and teaching, investigating and scrutinizing, and among these stallions is Imam Ahmad bin Salama Al-Shehab Al-Qaylubi Al-Masry Al-Shafi’i in his manuscript “Al-Marsa’ fi Fi Al-Four Madhhabs” in which he summarized the articles of the four jurists in various fields. Sub-doctrinal issues, so through this reading, I will try to reveal its essence and its secrets, and what is contained in it of precious and unique essence.